Implementasi Layanan Profilaksis Pra Pajanan (PrEP) Oral (Studi Kualitatif 2 Puskesmas di Kota Semarang) - Isnaeni, Rizka Nur; Kusumawati, Aditya; Handayani, Novia (Jurnal Kesehatan, 2024)
The trial implementation of the PrEP program as an HIV prevention program in Semarang City has not run optimally. Health workers with an essential role as program implementers still experience technical and technical obstacles in recording and reporting, which are quite complicated. It is necessary for a program that has been running for almost 3 years to carry out more in-depth studies, especially for health workers who play a direct role in providing PrEP services. Data collection was descriptive and qualitative, using in-depth interviews. The study subjects consisted of nine primary informants and four triangulated informants using purposive sampling. Data validity is carried out by triangulating data sources. Data reliability is measured by data audit and data analysis using the content analysis method. The study results show that health workers' implementation of the PrEP program differs from the management guidelines published by the Ministry of Health of the Republic of Indonesia in 2023. Most health workers have a low level of knowledge regarding the PrEP program and perceive that the PrEP program supports LGBT and free sex. As a result, intrapersonal conflict arises because it is considered to conflict with one's thought patterns and conscience. The conclusion is that the low level of knowledge among the majority of PrEP program implementers significantly influences the PrEP program's success. Therefore, there is a need for regular, more comprehensive training related to the PrEP program.